Investigating attitude and amount of contraceptive use during two years postpartum among women referring to health centers of Kermanshah - Sh Golyan Tehrani; B Khodakarami; G Babaie; A Hemati (Tehran University of Medical Sciences, 2004)
Introduction: Anually, 585000 women die from complications of pregnancy and childbirth in the world. Using postpartum contraceptive methods helps to prevent repeated pregnancies. Materials and Methods: This research is a descriptive and analytic cross-sectional study that has been performed among women who refered to health centers of Kermanshah city in 2002 to evaluate contraceptive use during two years postpartum and attitude toward it. In this study, some of health centers of Kermanshah city had been selected with cluster sampling and then 260 married women in fertility ages attending these health centers who had delivered during previous two years were selected, using stratified random sampling. Data collecting was performed by interview using a questionnaire that was consisted of 5 parts the data were analyzed using 2 and Fisher exact test, student T-test, Pearson and Logistic regression. Standard deviation (Sd) was reported for mean values. Results: The findings of this research indicated that 50.4% of women had a positive attitude toward using contraceptive methods during two years postpartum and 79.2% were using some contraceptive method. Husband education (p=0.036), having sexual activity (p=0.001), the time that has been elapsed from the last delivery (p=0.001), number of pregnancies (p=0.013), tendency to have more children (p=0.037), attitude toward contraceptive use (p=0.001), the type of breast feeding (exclusive or partial) (p=0.001), and quality of menstural cycles (p=0.001) were in relation to use of contraceptive methods during two years postpartum. Conclusion: According to these findings, attitudes and believes, breast feeding status and quality of menstural cycles play an essential role in postpartum contraception. Therefore, key steps to better family planning services at this time include effective counseling and starting training programs.